The Influence of Anxiety: A Study of the Postcolonial Memory and its Influence on the Indian Postcolonial Research - Das, Rituparna (Cahiers d'histoire)

(untitled) (Cahiers d'histoire, 2019)
My paper, is the compilation of the research findings obtained from interviews taken of various Postcolonial scholars. It spans the three generations of Postcolonial scholars including myself. It involves the study of two kinds of memory: firstly, the acquired memory or the memories that these scholars have, either from their own first hand experiences or from the information they had received from their forefathers who had the direct experience of this colonial past; secondly the collective formative memory or the memories they formed as a postcolonial nation from their school books, popular culture, film, theatre and literature. My paper aims to trace as to what extent, if at all, the effect of such colonial hangover has an impact on their research works. My paper would primarily be addressing the issue of the influence of colonial memory from three perspectives: the impact and result on the first generation Postcolonial scholars who grew up just at the brink of Indian independence; the impact and result on the second generation Postcolonial scholars who grew up during 1980’s and 90’s and who had access to the colonial memories from the oral narratives of their forefathers; the impact and result on today’s Postcolonial scholars who hardly have any colonial memories except what they had obtained from the text books and popular media. The result has some autobiographical elements as being a Postcolonial scholar myself, I have not been beyond the studies.